Study on Communal Wastewater Treatment Plants (CWWTPs) in Gresik, Indonesia - Soedjono, Eddy S. (International Journal of Integrated Engineering, 2019)
Communal wastewater treatment plants (CWWTPs) with sewer system has been built by local government in Gresik Regency to achieve sanitation strategy by 2012-2016. There are seven CWWTPS in Gresik; Bedilan, Singosari 1, Roomo, Sidorukun, Karangturi, Singosari 2, and Singosari 3. Each of CWWTP is maintained by the community and known as KPP (Kelompok Pengguna Pemelihara or community group of users and maintainers). CWWTPs have some operational problems due to minimum maintenance. Therefore, evaluation of CWWTPs is needed to determine whether field maintenance program complies with the guidelines. Efficiency in term of BOD removal for the 7 CWWTPs is between 79-96% and it complies with design criteria; except Bedilan CWWTP where removal of COD is 52.7% and it could not comply with the design criteria while removal of oil and grease is only up to 13%. One of the reasons for these failure was due to poor monitoring. Local communities have poor understanding regarding the duties and functions of KPP due to little information regarding KPP in the villages.